Analysis of the Benefits of Tutoring in Improving Student Learning Skills - Diadra Dewina Alti; Uli Makmun Hasibuan; Halimah Tusadiah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
This research aims to analyze the benefits of tutoring programs in helping to improve students' learning skills. This study used a qualitative method based on data collection and was carried out by reviewing several books, journals and other documents in print and electronic form. Tutoring is a process that involves a tutor or teacher who provides additional assistance in mastering lesson material. Tutoring can help students learn effective study techniques. Trained tutors can teach students different study methods such as creating a study schedule, reading with comprehension, taking notes, and mastering memory techniques. With this guidance, students will be able to improve their learning efficiency and achieve better results.